Cell T Regulator CD4 + CD25 + Increasing Tolerance of Donors and Recipients on Allogenic Transplantation - Muhaimin Rifa’i (Natural B, Journal of Health and Environmental Sciences, 2012)
To gain transplantation tolerance between donor and recipients is the ultimate goal of all transplantations, either solid or bone marrow transplantation. Activation and induction of regulatory T cells are shown to increase tolerance between donor and recipient. This study describes the importance of regulatory T cells, CD4+CD25+ in allogeneic bone marrow transplantation. Injection of bone marrow cells as much as (3-5) x 105 shown to increase donor T cell engraftments in recipient, both CD4 and CD8 populations. Naive T cells, CD4+CD62L+ cells increased in recipients receiving bone marrow co-transfer with regulatory T cells. In this study also demonstrated that granulocytes and B cells can better develop on a recipient that receives co-transfer of regulatory T cells. Interestingly, the cells that are resistant to radiation remain on the peripheral and does not interfere with the bone marrow. The results of this study could illustrate, at least partially, how naturally occurring Tregs exert their regulatory function in vivo as they constitute only 5 – 10% of peripheral CD4+ T cells.